2021
DOI: 10.1177/23259671211030473
|View full text |Cite
|
Sign up to set email alerts
|

Performance Outcomes After Surgical Repair of Achilles Tendon Rupture in the Women’s National Basketball Association

Abstract: Background: Achilles tendon ruptures are devastating in elite athletes. There are currently no studies examining the effects of Achilles tendon rupture on performance outcomes in the Women’s National Basketball Association (WNBA). Hypothesis: Athletes in the WNBA who sustained an Achilles tendon rupture and underwent subsequent surgical repair will sustain declines in performance metrics when compared with their preinjury statistics and matched controls. Study Design: Cohort study; Level of evidence, 3. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Achilles tendon ruptures have been considered one of the most detrimental injuries in professional basketball players, overall leading to shortened careers and significantly decreased performance following injury [1][2][3][4][5][6]. Earlier studies examined Achilles tendon ruptures in either all NBA or WNBA players, without specifically focusing on elite or higher-performing players based on their PER [2][3][4][5][6]. Prior research also did not explore the potential disparities in performance in NBA or WNBA players with dominant versus nondominant Achilles tendon ruptures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Achilles tendon ruptures have been considered one of the most detrimental injuries in professional basketball players, overall leading to shortened careers and significantly decreased performance following injury [1][2][3][4][5][6]. Earlier studies examined Achilles tendon ruptures in either all NBA or WNBA players, without specifically focusing on elite or higher-performing players based on their PER [2][3][4][5][6]. Prior research also did not explore the potential disparities in performance in NBA or WNBA players with dominant versus nondominant Achilles tendon ruptures.…”
Section: Discussionmentioning
confidence: 99%
“…Players also exhibited a decline in minutes and games played, coupled with notably shorter careers compared to age-matched controls. A comparable study conducted on Women’s National Basketball Association (WNBA) players revealed similar outcomes, with only 83% of players returning to play after rupture and experiencing diminished performance post-injury [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, this study conducted a power analysis paralleling methodology of previous studies that explored changes in PER for other NBA knee injuries. 10 , 18 A sample size of 6 was deemed acceptable to power this study (⍺ = 0.05, power = 0.8, standard deviation = 3). Three of the 9 injured players were excluded from analysis, with 2 suffering career-ending quadriceps tendon injuries, and the other having sustained his injury during the 2020-2021 season.…”
Section: Methodsmentioning
confidence: 99%